Investigating the Levels of Polychlorinated Biphenyls (PCBs) at Three Lactational stages: A comprehensive Study in Ghana - Jonathan, Justice Wiston Amstrong; Kabotso, Daniel Elorm Kwame; Essumang, David Kofi; Bentum, John Kwesi; Ofosu-Koranteng, Francis; Mbroh, Hintermann; Tampuori, John (Archives of Clinical and Medical Case Reports, 2024)
Background: The human breast secretes three types of milk during lactation – colostrum, transitional milk and mature milk. However, like any other biofluid, human breast milk is not pristine. Objective: The objective of this study was to determine the levels of polychlorinated biphenyls congeners in colostrum, transitional milk and mature milk of mothers at the Ho Teaching Hospital to ascertain which portion contained the highest levels of PCBs that could pose any significant health risks to neonates. Methods: A cross-sectional study design was employed to conduct the study. Protocol for the study was reviewed and approved by the University of Health and Allied Sciences Research Ethics Committee (UHAS–REC), Protocol Number UHAS-REC A.9 [6] 19-20 The study recruited fortyseven (47) mothers using purposive sampling, with each mother donating 12 mL of colostrum, transitional milk and mature milk, making a total of 141 milk samples. About 10.0 g of each aliquot of breast milk sample was treated using QuEChERS method to extract PCBs and the resulting extract analyzed for fourteen (14) PCB congeners using GC–MS/MS. Results: All the samples had PCB levels below thresholds of detection. The lack of PCB residues in the examined milk samples may be viewed as positive news. It might suggest that the mothers were only minimally exposed to these industrial pollutants. Conclusions: At any stage of lactation, no PCB residues were found in the breast milk samples examined. Thus, there were no obvious health concerns for breastfed infants from PCBs contamination of mothers’ milk.